1998
DOI: 10.1021/bi980764f
|View full text |Cite
|
Sign up to set email alerts
|

Transient Kinetic Studies on the Interaction of Ras and the Ras-Binding Domain of c-Raf-1 Reveal Rapid Equilibration of the Complex

Abstract: Transient kinetic methods have been used to analyze the interaction between the Ras-binding domain (RBD) of c-Raf-1 and a complex of H-Ras and a GTP analogue. The results obtained show that the binding is a two-step process, with an initial rapid equilibrium step being followed by an isomerization reaction occurring at several hundred per second. The reversal of this step determines the rate constant for dissociation, which is on the order of 10 s-1. The lifetime of the complex is therefore on the order of 50-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
112
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 124 publications
(131 citation statements)
references
References 30 publications
17
112
0
2
Order By: Relevance
“…Therefore, as [Raf] increases, the Raf -RasGTP binding reaction also becomes faster, thereby increasing the rate at which RasGTP is depleted. Similarly, Sydor et al [43] have shown that the Raf -Ras complex has an extremely short lifetime, after which Raf is released for downstream signalling. The resulting Ras species, denoted RasGTP Ã , is no longer capable of activating Raf and will undergo GTP hydrolysis catalysed by GTpase activating proteins (GAPs), which are recruited to focal adhesions after integrin-ligand binding [44,45].…”
Section: Ras and Raf As Regulators Of Erk Activitymentioning
confidence: 87%
“…Therefore, as [Raf] increases, the Raf -RasGTP binding reaction also becomes faster, thereby increasing the rate at which RasGTP is depleted. Similarly, Sydor et al [43] have shown that the Raf -Ras complex has an extremely short lifetime, after which Raf is released for downstream signalling. The resulting Ras species, denoted RasGTP Ã , is no longer capable of activating Raf and will undergo GTP hydrolysis catalysed by GTpase activating proteins (GAPs), which are recruited to focal adhesions after integrin-ligand binding [44,45].…”
Section: Ras and Raf As Regulators Of Erk Activitymentioning
confidence: 87%
“…In typical stopped-flow binding measurements, the protein and ligand are rapidly mixed, and the extent of the reaction is monitored as a function of time using techniques including spectroscopic absorbance (21), fluorescence (10,26,27), enzymatic activity (1,28,29), and surface plasmon resonance (30,31). These techniques are limited by the requirement that the lifetimes of the free and bound states must be severalfold longer than the time required to completely mix the protein and ligand solutions; otherwise, the reaction proceeds nearly to completion before the start of the measurement period.…”
mentioning
confidence: 99%
“…Ras has a net negatively charged binding site, whereas the effector RBDs have a net positively charged binding site. As a result, the rate of association between them was found to be very high and contributes significantly to the affinity of the complex (6,7). Furthermore, differences in binding affinities for some of the Ras͞effector complexes are a consequence of different association rate constants, with the dissociation rate constants being at a similar range (6,7).…”
mentioning
confidence: 99%
“…As a result, the rate of association between them was found to be very high and contributes significantly to the affinity of the complex (6,7). Furthermore, differences in binding affinities for some of the Ras͞effector complexes are a consequence of different association rate constants, with the dissociation rate constants being at a similar range (6,7). For example, the high, nanomolar affinity of the binding of Raf-RBD to Ras is attributed to the very high k on value, which stems from the strong electrostatic complementarity between the Ras͞Raf-RBD binding sites.…”
mentioning
confidence: 99%